PERAN SANGGAR MULYA BAKTI DALAM PELESTARIAN TARI TOPENG DI INDRAMAYU TAHUN 2005-2015 - Umami, Riza; Sujati, Budi (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This study aims to explain the role of Sanggar Mulya Bhakti in the preservation of Mask Dance in Indramayu in 2005-2015. The research method used is the historical method, namely: heuristics, criticism, interpretation and historiography. The Mulya Bhakti studio was first established in 1983, which is located in the village of Tambi, Sliyeg, Indramayu Regency. The Mulya Bhakti studio is one of the existing art studios and continues to this day, this studio continues to preserve traditional arts, especially mask dance, amidst the many foreign cultures that have entered Indonesia without exception to the village of Tambi, Sliyeg Indramayu. Sanggar Mulya Bhakti has a role in the development of mask dance by means of preservation, performance and training. Suggestions from the results of this study are for Sanggar Mulya Bhakti, to further improve Mask Dance training, to improve administration, for the government and society to participate in promoting and preserving Mask Dance in Indramayu Regency.